Simulation Analyses on a Downburst Event That Caused a Severe Tower Toppling down Accident in Zhejiang (China) - Danyu Li; Jinghua Liu; Bin Liu; Wenqi Fan; Dongwen Yang; Xue Xiao (Atmosphere, 2023)
The downburst events have been a research focus for decades, as their associated disastrously strong winds pose a great threat to aviation, the shipping industry, agriculture, and the power industry. On 14 May 2021, a series of severe convection occurred in middle and eastern China, during which six 500-kilovolt transmission line towers in Zhejiang were toppled down by a downburst event, resulting in a large range of power outages. By using the Weather Research and Forecasting (WRF) model version 4.4, key features of the downburst event were reproduced reasonably; based on which, we explored the evolutionary mechanisms and the three-dimensional structures of the strong winds associated with the downburst event. It was found that a southwest–northeast-orientated, eastward moving strong squall line was the parent convection system for the downburst event. The downburst-associated convection was deep (from surface to 200 hPa); in the near surface layer, it was mainly associated with positive geopotential height and negative temperature deviations, whereas, at higher levels, it was mainly associated with negative geopotential height and positive temperature deviations. Backward trajectory analysis indicates that the air particles that came from the middle troposphere west of the key region (~61.2% in proportion) were crucial for producing the strong winds of the downburst event. These air particles experienced notable descending processes, during which most of the air particles decreased notably in their potential temperature, while they increased significantly in their specific humidity. The kinetic energy budget analyses denote that, for the region surrounding the location where the tower toppling appeared, the work done by the strong pressure gradient force between the high-pressure closed center (corresponding to intense descending motions) and the low-pressure closed center (corresponding to strong latent heat release) dominated the rapid wind enhancement.